Facial esthetics in children with unilateral cleft lip and palate 3 years after alveolar bonegrafting combined with rhinoplasty between 2 and 4 years of age. (17th September 2012) - Offert, B.; Janiszewska‐Olszowska, J.; Dudkiewicz, Z.; Brudnicki, A.; Katsaros, C.; Fudalej, P. S.
Abstract : Offert B., Janiszewska‐Olszowska J., Dudkiewicz Z., Brudnicki A., Katsaros C., Fudalej P. S. Facial esthetics in children with unilateral cleft lip and palate 3 years after alveolar bonegrafting combined with rhinoplasty between 2 and 4 years of age   Orthod Craniofac Res 2013;16 :36–43. © 2012 John Wiley & Sons A/S Structured Abstract: Objectives –  To evaluate facial esthetics in patients with unilateral cleft lip and palate (UCLP) after alveolar bone grafting combined with rhinoplasty between 2 and 4 years of age. Design –  Retrospective case‐control study. Setting –  The Department of Pediatric Surgery, Institute of Mother and Child, Warsaw, Poland. Material and Methods –  Photographs of full faces and cropped images of five nasolabial components: nasal deviation, nasal form, nasal profile, vermillion border, and inferior view were assessed by 5 professional and 14 layraters in 29 children (23 boys and 6 girls; mean age = 5.3 years, SD 0.5; Early‐grafted group) and 30 children (20 boys and 10 girls; mean age = 5.5 years, SD 1.0; Non‐grafted group) with complete unilateral cleft lip and palate repaired with a one‐stage closure. The groups differed regarding the timing of alveolar bone grafting: in the Early‐grafted group, alveolar bone grafting in combination with rhinoplasty (ABG‐R) was performed between 2 and 4 years of age (mean age = 2.3 years; SD 0.6); in the Non‐grafted group, the alveolar defect was grafted after 9 years of age. No primary nose correction was carried out in any group. To rate esthetics, a modified five‐grade esthetic index of Asher‐McDade was used, where grade 1 means the most esthetic and grade 5 – the least esthetic outcome. Results –  Esthetics of full faces and of all nasolabial elements in the Early‐grafted group was significantly better than in Non‐grafted group. The scores in the Early‐grafted group ranged from 2.30 to 2.66 points, whereas in the Non‐grafted group ranged from 2.66 to 3.17 points. All intergroup differences were statistically significant ( p  < 0.05). Conclusions –  Three years post‐operatively, early alveolar bone grafting combined with rhinoplasty is favorable for facial esthetics in children with UCLP, but a longer follow‐up is needed to assess whether the improvement was permanent.